2022
DOI: 10.1108/ccij-11-2021-0125
|View full text |Cite
|
Sign up to set email alerts
|

How environmental gain messages affect cause involvement, attitude and behavioural intentions: the moderating effects of CSR scepticism and biospheric values

Abstract: PurposeThis study examines the direct effect of outcome message frames (gain vs loss) on cause involvement and the moderating roles of consumers' corporate social responsibility (CSR) scepticism and biospheric values. Furthermore, the authors analyse (1) the effects of gain-framed messages on consumer attitudes towards an environmental cause (i.e. the use of reusable coffee cups) and towards the company promoting the cause (a coffee shop chain); (2) how consumer attitudes towards the cause affect their attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 58 publications
2
8
0
Order By: Relevance
“…Adopting the repurposed design strategy can help hospitality and tourism organizations achieve sustainability goals and convey responsible corporate value through the servicescape tangibles. At the same time, repurposed servicescape designs may evoke biospheric values, which has been demonstrated to foster customers’ cause involvement (Stadlthanner et al, 2022). Yet, whether and why repurposed design strategy would influence customer responses in terms of inspiration and repurchase intention remain an under-explored topic in the hospitality and tourism literature, and awaits theoretical explorations.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Adopting the repurposed design strategy can help hospitality and tourism organizations achieve sustainability goals and convey responsible corporate value through the servicescape tangibles. At the same time, repurposed servicescape designs may evoke biospheric values, which has been demonstrated to foster customers’ cause involvement (Stadlthanner et al, 2022). Yet, whether and why repurposed design strategy would influence customer responses in terms of inspiration and repurchase intention remain an under-explored topic in the hospitality and tourism literature, and awaits theoretical explorations.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Prior studies by Pomering and Dolnicar (2009), Palihawadana et al (2016), Cerkasov et al (2017) and Collins and Kug (2021) found that CA is a determinant of consumers' future behaviour. Besides, the results of some recent studies indicated that CA and CB are influenced positively when consumers are aware of the businesses and their initiatives (Olšanov a et al, 2022;Stadlthanner et al, 2022). For instance, there is evidence that consumers who are concerned about environmental issues are more likely to buy green products (do Paço et al, 2019).…”
Section: Impact Of Consumer Attitude On Consumer Purchasing Behaviourmentioning
confidence: 99%
“…Most recently, Ng (2022) investigated how perceived CSR relate to CA regarding social enterprise products and found positive effects. Both Stadlthanner et al (2022) and Lee and Lin (2022) studied how CSR advertisements affect CA and found a positive significant influence.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Therefore, communicating anti-consumption to consumers is essential to drive radical changes. Marketing communication represents a significant tool for inducing behaviour change among consumers (Goldberg and Gustafson, 2023) especially in the context of sustainability (Mee and Clewes, 2004; Stadlthanner et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%